Effect of Metronidazole on the Growth of Vaginal Lactobacilli in vitro - Jose A. Simoes; Alla A. Aroutcheva; Susan Shott; Sebastian Faro (Hindawi Limited, 2001)
Objective: To determine whether metronidazole has an adverse effect on the growth of Lactobacillus.